The Constitutional Court in Algeria - Abdennour, Sihem (Journal of Human Sciences, 2023)
Through a constitutional amendment in 2020, the founder of the Constitution abolished the Constitutional Council and created a new body, the Constitutional Court, considered a supreme control body. This modification concerns not merely the name but also the composition and powers. Furthermore, it responds to the political and general desire to activate the role of political authorities and regulatory bodies.The Constitutional Court comprises 12 members, with specific requirements and processes described in the constitutional amendment. It is a supreme supervisory body responsible for assessing the legality of legislation and studying the conformity of laws and regulations with the Constitution, among other things. This is seen as a guarantee of the constitutional primacy concept and the consecration of the rule of law.